Choroidal Tuberculoma in a Healthy Immunocompetent Patient - Gurung, Hara Maya; Gurung, Krishna; Gurung, Anju; Maharjan, Indraman; Shrestha, Eliya; Gurung, Babita; Adhikari, Hari Bikram; Nemkul, Saroj Prasad (Nepalese Journal of Ophthalmology, 2021)
Introduction: Ocular tuberculosis as choroidal tuberculoma is a rare event. It creates a clinical diagnostic dilemma when there is no systemic involvement. Case: A 22-year-old man presented with the chief complaints of discomfort and blurring of vision of right eye for one week. On fundus examination under mydriatics of his right eye, a solitary mass which measured approximately 2DD (Disc Diameter) was appreciated at the superotemporal quadrant with the surrounding localized retinal detachment. Choroidal tuberculoma was suspected by a positive Mantoux test. Physician consultation and laboratory investigations ruled out the pulmonary and systemic manifestation of tuberculosis and other aetiology. Anti-tubercular treatment was started and this led to the improvement of vision and shrinkage of the choroidal mass into a flat chorioretinal scar at 3 months of anti-tubercular treatment . Conclusion: Solitary choroidal tuberculoma though rare, can occur in a healthy, immunocompetent patient.